Gender Equality : Which Policies Have the Biggest Bang for the Buck? - Jain-Chandra, Sonali (IMF Working Papers; Working Paper ;, 2018)
This paper analyzes the relationship between fiscal and structural policies and gender inequality in education and labor force participation for countries at different stages of development. Due to the substantial number of possible factors that link with gender inequality previously highlighted in the literature, we pay particular attention to addressing model uncertainty and using various statistical methods to find the variables with the strongest links to gender gaps. We find that higher public spending on education, better sanitation facilities, low adolescent fertility, and narrower marriage age gaps are significantly related to narrower gender gaps in education. We also find that better infrastructure, a stronger institutional environment, more equal legal rights, and low adolescent fertility rates are strongly associated with higher female labor force participation. When labor market protection is low, an increase in protection is associated with a narrowing of labor force participation gaps between men and women. But when labor market protection levels are high, an increase in protection is associated with a widening in labor force participation gaps.